Anxiety and Depression among Hypertensive Outpatients in Afghanistan: A Cross-Sectional Study in Andkhoy City - Mohammad Shoaib Hamrah; Mohammad Hassan Hamrah; Hideki Ishii; Susumu Suzuki; Mohammad Hussain Hamrah; Ahmad Edris Hamrah; Ahmad Elias Dahi; Kyosuke Takeshita; Maimaiti Yisireyili; Mohammad Hashem Hamrah; Akbar Fotouhi; Junichi Sakamoto; et al. (International Journal of Hypertension)
There is a relationship between mental and physical health. Depression and anxiety are linked with the development of several chronic diseases. The purpose of the present study was to determine the prevalence and factors associated with anxiety and depression among adult hypertensive outpatients in Afghanistan. Methods. Two hundred thirty-four consecutive hypertensive patients from December 2015 to August 2016 were recruited to complete the Hospital Anxiety and Depression Scale (HADS) questionnaire, which has scores for classifying the participants having anxiety and depression symptoms. Results. Of the total 234 patients, 81 (34.6%) were males and 153 (65.4%) were females. The mean age was 54.6±12.7 for the hypertensive patients with anxiety and 63.8±15.0 for the hypertensive patients with depression while this figure was 49.5±10.2 for the adult participants in general population in Kabul city (Saeed, 2013). The prevalence of anxiety and depression (42.3% vs. 58.1%) among hypertensive persons is compared with the same mental disorders among Afghan refugees (39.3% vs. 22.1%) in Dalakee Refugee Camp (in Iran) (Hosseini Divkolaye and Burkle, 2017). Of the total participants, 99 had anxiety (42.3%), 136 had depression (58.1%), and 66 had (28.2%) comorbid anxiety-depression. Multivariate analysis was used. For anxiety age, female gender, smoking, diabetes mellitus, and 2 or more chronic diseases had a significant association. For depression, age and diabetes mellitus had a significant association, and for comorbid anxiety, depression, age, diabetes mellitus, and 2 or more chronic diseases had a significant association. Conclusion. This study shows that anxiety and depression are highly prevalent among hypertensive patients in an outpatient clinic in Afghanistan. There was an association between some sociodemographic and clinical characteristics and anxiety and depression. More studies are needed on a national level to inform the development of strategies for the prevention and control of psychological distress among patients with chronic diseases in Afghanistan.